Antismoking education in Czech medical and dental faculties - Hrubá, D; Slezák, R (European journal of dental education, 2004)
Smoking education has been included in the curricula in all the medical faculties of the Czech Republic, although the scope of the education varies. At each of the faculties, a member of the staff has been appointed as co-ordinator of smoking education. These coordinators promote a sharing of experience and distribution of teaching materials. At the majority of faculties, obligatory workshops are held for all students to learn about smoking and smoking treatment within the framework of preventive medicine. In addition, selected students undertake selected studies on smoking and health as part of their research. At the Medical Faculty of Masaryk University, Brno, smoking education is included in the majority of theoretical and clinical subjects and its effectiveness is repeatedly assessed during the 6-year course study by testing the students' knowledge and smoking behaviour. The evaluation provides a basis for further modification and improvement of the education. Currently, a fundamental transformation of dental education is being undertaken in all medical faculties of the Czech Republic. These new curricula will benefit from the curriculum of the Medical Faculty, at Hradec Králové, where the changes that were made 5 years ago involve theoretical and practical education in the risks of smoking for oral health throughout the 5-year stomatology courses. Postgraduate medical education involves professional 2-day seminars for general practitioners on approaches to smoking cessation and smoking dependence treatment, and professional materials such as smoking cessation guidelines are published in medical and specialist journals.
Keywords: studium lékařství specializační postgraduální; Curriculum; Education, Dental, Graduate; Humans; kurikulum; Female; Attitude to Health; postoj ke zdraví; studium lékařství; prevence kouření; Education, Medical, Graduate; lidé; učební pomůcky; odvykání kouření; studium stomatologie; Smoking Cessation; Teaching Materials; ženské pohlaví; Male; Education, Dental; vyučování; Czech Republic; školy stomatologické; Schools, Dental; studium stomatologie specializační postgraduální; školy lékařské; Teaching; Česká republika; mužské pohlaví; Education, Medical; Schools, Medical; Smoking Prevention